Conditioning of stress in Nile tilapia - Moreira, PSA; Volpato, G. L. (Blackwell Publishing, 2004)
A Pavlovian conditioning paradigm was used to induce a connection between a conditioned stimulus, light (CS), associated with an unconditioned stimulus, confinement (US) in Nile tilapia Oreochromis niloticus, which resulted in a conditioned endocrine response (CR) to the CS alone manifested as an increase in plasma cortisol. Individual isolated Nile tilapia were submitted for 10 days to the conditioning treatment consisting of turning on a light (CS) for I min with subsequent 30 min confinement (US). on the 10th day of the experiment, plasma cortisol was not increased when fish were subjected to no handling at all, or only light, or even a daily stressor for the 9 days. on the other hand, at the 10th day cortisol was significantly increased only when light was presented either with or without pairing with the stressor. These results confirmed that the cue, light (CS), was not stressful in itself, but when given as the CS in the absence of the US post conditioning the hypothalamus-pituitary-interrenal axis was activated. Therefore, it was concluded that memory of a previous experience with a stressor can be recalled by a conditioned stimulus and induce stress, which is the first demonstration of a memory-induced stress in fishes. (C) 2004 the Fisheries Society of the British Isles.
Keywords: animal welfare; cortisol; memory; Nile tilapia; Pavlovian conditioning